Dual-energy computed tomography in calcium pyrophosphate deposition: initial clinical experience. Issue 9 (September 2019) - Pascart, T.; Norberciak, L.; Legrand, J.; Becce, F.; Budzik, J.-F.
Summary: Objective: To determine the dual-energy computed tomography (DECT) attenuation properties of meniscal calcifications in calcium pyrophosphate deposition (CPPD) in vivo, and assess whether DECT was able to discriminate meniscal CPP deposits from calcium hydroxyapatite (HA) in subchondral and trabecular bone. Method: Patients with clinical suspicion of crystal-related arthropathy (gout and/or CPPD) and knee DECT scans were retrospectively assigned to CPPD ( n  = 19) or control ( n  = 21) groups depending on the presence/absence of chondrocalcinosis on DECT. Two observers drew standardized regions of interest (ROI) in meniscal calcifications, non-calcified menisci, as well as subchondral and trabecular bone. Five DECT parameters were obtained: CT numbers (HU) at 80 and 140 kV, dual-energy index (DEI), electron density (ρe ), and effective atomic number (Zeff ). The four different knee structures were compared within/between patients and controls using linear mixed models, adjusting for confounders. Results: Meniscal calcifications ( n  = 89) in CPPD patients had mean ± SD CT numbers at 80 and 140 kV of 257 ± 64 and 201 ± 48 HU, respectively; with a DEI of 0.023 ± 0.007, and ρe and Zeff of 140 ± 35 and 8.8 ± 0.3, respectively. Meniscal CPP deposits were readily distinguished from calcium HA in subchondral and trabecular bone ( p  ≤ 0.001), except at 80 kV separately ( p  = 0.74). Zeff and ρe both significantly differed between CPP deposits and calcium HA in subchondral and trabecular bone ( p  < 0.0001). Conclusion: This proof-of-concept study shows that DECT has the potential to discriminate meniscal CPP deposits from calcium HA in subchondral and trabecular bone in vivo, paving the way for the non-invasive biochemical signature assessment of intra- and juxta-articular calcium crystal deposits.